ANALISIS PRODUKTIVITAS PER SATUAN VOLUME USAHA PEMBESARAN IKAN NILA (OREOCHROMIS NILOTICUS) BERBASIS TEKNOLOGI BIOFLOK DI KABUPATEN GARUT - Nanda Helisa; Asep Agus Handaka Suryana; Junianto Junianto; Ine Maulina (Universitas Mataram, 2026)
Bioflox technology is an intensive aquaculture innovation that can improve space utilization efficiency through water management, stocking density, and the use of microorganisms in the rearing medium. This study aims to analyze productivity per unit volume in tilapia (Oreochromis niloticus) grow-out operations using biofloc technology in Garut Regency. This study was conducted in four sub-districts: Pangatikan, Sukawening, Wanaraja, and Kersamanah. The method used was a survey employing a quantitative descriptive approach. Data were collected through interviews, observations, and documentation from 37 respondents representing a total of 81 biofloc pond units. Productivity per unit volume was calculated based on the ratio of total tilapia production to pond volume a single cultivation cycle. The results indicated that there were differences were influenced by variations in pond size, production volume, stocking density, seed quality, feed management, and water quality management. The highest productivity was found in Pangatikan Subdistrict at 21.7 kg/m3/cycle, while other subdistricts showed varying productivity values according to their respective technical aquaculture conditions. The findings of this study indicate that tilapia farming using biofloc technology in Garut Regency has good productivity potential because it can yield high production in limited pond volumes, however it still requires optimal technical management.